2008
DOI: 10.1007/s10877-008-9154-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Forehead Venous Pressure as a Measure of Respiratory Effort for the Diagnosis of Sleep Apnea

Abstract: The results of the study suggest that the FVP can serve as an alternative to respiratory bands in the differential diagnosis of sleep disordered breathing, and in the recognition of patients appropriate for bilevel continuous positive airway pressure devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It has been shown that intensity variations of the PPG signal may be induced by respiration [60]. Although the physiological background of respiratory-induced intensity variations is not fully understood, it is assumed that the fluctuation of venous return to the heart, linked to the alterations in intrathoracic pressure, is a dominant mechanism [61]. The peak-to-peak amplitude of these respiratoryinduced intensity variations is closely correlated with tidal volume and respiratory changes in peripheral venous pressure.…”
Section: Forehead Venous Pressure (Fvp)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that intensity variations of the PPG signal may be induced by respiration [60]. Although the physiological background of respiratory-induced intensity variations is not fully understood, it is assumed that the fluctuation of venous return to the heart, linked to the alterations in intrathoracic pressure, is a dominant mechanism [61]. The peak-to-peak amplitude of these respiratoryinduced intensity variations is closely correlated with tidal volume and respiratory changes in peripheral venous pressure.…”
Section: Forehead Venous Pressure (Fvp)mentioning
confidence: 99%
“…PPG applied to the forehead is believed to monitor respiration-related changes of volume or pressure in the veins of the skin. Using a commercial device (ARES™ Unicorder, Advanced Brain Monitoring, Carlsbad, CA), PPG has been applied in a trial to validate forehead venous pressure (FVP) as a measure of respiratory effort for the diagnosis of sleep apnea [61]. The monitoring of FVP is based on a composite signal derived from optical, motion and pressure sensors.…”
Section: Forehead Venous Pressure (Fvp)mentioning
confidence: 99%
“…Inlaboratory PSG is also not practical in some situations, such as postoperative sleep evaluation. To deal with this issue, a number of portable sleep monitoring devices have been developed [15][16][17][18][19][20]. To provide evidence-based recommendations on the use of unattended portable monitors in the diagnosis of obstructive sleep apnea in adult patients, a clinical guideline has been published by the Portable Monitoring Task Force of the American Academy of Sleep Medicine in 2007 [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Participants will be eligible if they continue to have insomnia once adherent to positive airway pressure ≥ 6 hours/night for at least 3 months. Those who have not been evaluated for SA will be screened in their homes with the Apnea Risk Evaluation System (ARES) [36], a portable sleep recorder for two consecutive nights. If participants have previous SA apnea screening within the past year that meets the study criteria, we will include them in the study.…”
Section: Methodsmentioning
confidence: 99%